Host genetics and gut microbiota influence lipid metabolism and inflammation: potential implications for ALS pathophysiology in SOD1G93A mice - Elena Niccolai; Leandro Di Gloria; Maria Chiara Trolese; Paola Fabbrizio; Simone Baldi; Giulia Nannini; Cassandra Margotta; Claudia Nastasi; Matteo Ramazzotti; Gianluca Bartolucci; Caterina Bendotti; Giovanni Nardo; et al. (Acta Neuropathologica Communications)
Abstract Amyotrophic Lateral Sclerosis (ALS) is a devastating neurodegenerative disorder characterized by the progressive loss of motor neurons, with genetic and environmental factors contributing to its complex pathogenesis. Dysregulated immune responses and altered energetic metabolism are key features, with emerging evidence implicating the gut microbiota (GM) in disease progression. We investigated the interplay among genetic background, GM composition, metabolism, and immune response in two distinct ALS mouse models: 129Sv_G93A and C57Ola_G93A, representing rapid and slow disease progression, respectively. Using 16 S rRNA sequencing and fecal metabolite analysis, we characterized the GM composition and metabolite profiles in non-transgenic (Ntg) and SOD1G93A mutant mice of both strains. Our results revealed strain-specific differences in GM composition and functions, particularly in the abundance of taxa belonging to Erysipelotrichaceae and the levels of short and medium-chain fatty acids in fecal samples. The SOD1 mutation induces significant shifts in GM colonization in both strains, with C57Ola_G93A mice showing changes resembling those in 129 Sv mice, potentially affecting disease pathogenesis. ALS symptom progression does not significantly alter microbiota composition, suggesting stability. Additionally, we assessed systemic immunity and inflammatory responses revealing strain-specific differences in immune cell populations and cytokine levels. Our findings underscore the substantial influence of genetic background on GM composition, metabolism, and immune response in ALS mouse models. These strain-specific variations may contribute to differences in disease susceptibility and progression rates. Further elucidating the mechanisms underlying these interactions could offer novel insights into ALS pathogenesis and potential therapeutic targets.